2021
DOI: 10.1038/s41598-021-99741-8
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota and microbial metabolites are associated with tail biting in pigs

Abstract: Tail biting is an abnormal behaviour that causes stress, injury and pain. Given the critical role of the gut-microbiota in the development of behavioural problems in humans and animals, the aim of this study was to determine whether pigs that are biters, victims of tail biting or controls (nine matched sets of pigs) have a different microbiota composition, diversity and microbial metabolite profile. We collected faecal and blood samples from each individual for analysis. The gut microbiota composition was most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 91 publications
1
20
0
Order By: Relevance
“…The association between microbiota and behaviour is increasingly studied and accumulating evidence indicates that the gut microbiota can influence animal behaviour 3 , 5 , 8 , 13 , 15 , although the underlying mechanisms largely remain to be deciphered. We previously investigated the influence of diet on gut microbiota and host mucosa development during early life in pigs 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between microbiota and behaviour is increasingly studied and accumulating evidence indicates that the gut microbiota can influence animal behaviour 3 , 5 , 8 , 13 , 15 , although the underlying mechanisms largely remain to be deciphered. We previously investigated the influence of diet on gut microbiota and host mucosa development during early life in pigs 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its value as a translational model for human development, disease and the underlying processes, the understanding of early-life development in pigs is also valuable in the context of veterinary and animal sciences. However, there are only a handful of studies 13 15 evaluating the relationship between microbial communities and behavioural characteristics in pigs, reflecting the putative communication with the gut and the brain.…”
Section: Introductionmentioning
confidence: 99%
“…For example, poor litter quality has been associated with HN injuries ( Marchewka et al, 2019 ), BT injuries ( Leishman et al, 2022 ), and FP injuries ( Ekstrand and Algers, 1997 ; Bergmann et al, 2013 ; Da Costa et al, 2014 ), which may contribute to co-occurrence of these injuries. Alternatively, there may be specific bird characteristics that make individuals more likely to be a victim, similar to actors and receivers of feather pecking in laying hens ( van Staaveren and Harlander, 2020 ) or tail biting in pigs ( Brunberg et al, 2013 ; Verbeek et al, 2021 ). Experimental and/or longitudinal studies are needed to determine if there is a causative order in these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the swine gut microbiome have largely benefited from the establishment of a reference gene catalogue by means of deep metagenome sequencing of fecal samples [ 102 ] and have confirmed that also in this livestock species the interplay between diet and gut physiology across different growth stages is intimately associated with animal health and production performance [ 103 ], including fat deposition [ 104 ]. Other than varying on the basis of the food provided [ 105 , 106 , 107 , 108 ], GIT location [ 109 , 110 , 111 ], behavior [ 112 ], parasite infections [ 113 ], breed affiliation, and sex [ 114 ], the microbial diversity was found to correlate positively with piglet weight [ 115 ] and age [ 116 ]. Likewise, studies combining 16S rRNA metabarcoding and shotgun metagenomic sequencing revealed that the composition of the pig gut microbiome varies considerably and predictably across the lifespan [ 117 ].…”
Section: Microbiome Studies In Livestock Speciesmentioning
confidence: 99%
“…Notwithstanding the pronounced GIT structural differences between ruminants and monogastric animals such as pigs, the gut microbiome of the latter is also dominated by phyla Bacteroidetes and Firmicutes [ 115 ], followed by Proteobacteria [ 103 , 112 ], with Bacteroidia and Clostridia being the most abundant classes along with Bacilli [ 112 , 124 ]. Similar to what was observed in other livestock species, the dominant orders are Bacteroidales and Clostridiales ( Figure 2 ), while the most abundant families are Bacteroidaceae, Enterobacteriaceae, Lachnospiraceae, Lactobacillaceae, Prevotellaceae, and Ruminococcaceae [ 106 , 108 , 116 ].…”
Section: Microbiome Studies In Livestock Speciesmentioning
confidence: 99%